CFD investigation on wheel rotation modelling. Issue 174 (March 2018) - Hobeika, Teddy; Sebben, Simone
Abstract: It is well understood in the automotive community that wheels are a major contributor to the aerodynamic drag of passenger vehicles. The flow around rotating wheels is very complex due to the many separation regions created by very small tyre features and by the contact area of the tyre with the ground. Correct modelling of wheel rotation requires accuracy in the representation of the tyre geometry and proper boundary conditions to simulate the rotation. This paper proposes a hybrid approach for simulating tyre rotation which is simple to implement and does not suffer from the limitations of a sliding mesh approach, at the region where the tyre meets the ground. The method is first evaluated on a single wheel that is free standing and the results are compared to a full sliding mesh computation, which is considered to be the best possible numerical solution. The technique is then implemented on a complete vehicle model simulation and the results are compared against wind tunnel force measurements. The good agreement obtained in these test cases shows that the proposed approach is a promising solution to a more accurate numerical simulation of rotating wheels. Highlights: Moving Reference Frame - grooves (MRFg) approach for modelling tyre rotation is presented. Modelling results are compared to the sliding mesh approach on a freely rotating isolated wheel. MRFg shows good agreement with experimental force measurements on a full scale vehicle.